Impact of Preoperative Hair Removal on Surgical Site Infection in Elective Abdominal Surgery - Saxena, Anuj; Panda, Kedarnath; Bhoi, Suraj Kumar (Student’s Journal of Health Research Africa, 2024)
Background: Hair removal before surgery is common to avoid surgical site infections. The impact of this approach on SSI rates, especially in elective abdominal procedures, is debatable. This study aims to evaluate the impact of preoperative hair removal on the incidence of SSI and postoperative pain in patients undergoing elective abdominal surgeries. Methods: A prospective comparative cohort study involved two hundred patients undergoing elective abdominal surgery were divided into two groups: Group A (preoperative hair shaving) and Group B (no preoperative hair shaving). Demographic data, SSI incidence, and pain during dressing changes were recorded and analyzed using chi-square, Fisher’s exact test, and Mann–Whitney U test. Results: The incidence of SSI in Group A was 8% on day 7, 10% on day 14, and 12% on day 30, compared to 4%, 6%, and 8%, respectively, in Group B. However, these differences were not statistically significant (p > 0.05). Pain during dressing changes was significantly higher in Group A, with a mean VAS score of 3.8 ± 1.2 compared to 2.7 ± 1.1 in Group B (p < 0.001). Subgroup analysis revealed no significant difference in SSI rates between clean and clean-contaminated surgeries within each group. Clean surgeries in Group A had an SSI rate of 4%, while Group B had 2%. Clean-contaminated surgeries had an SSI rate of 16% in Group A and 12% in Group B, with no statistically significant differences (p > 0.05). Conclusion: Preoperative hair removal increases dressing change pain but does not affect elective abdominal surgery SSI rates. The findings show that standard preoperative hair removal may not be necessary and might be reconsidered to improve patient comfort. Recommendations: Further research with larger sample sizes and extended follow-up periods is recommended to confirm these findings and develop evidence-based guidelines for preoperative hair removal practices.